The early development of a combined micro- and full-field X-ray fluorescence analysis system using white X-rays at PLS-II - Min Woo Kim; Kangwoo Ahn; Chang Hun Lee; Tae Joo Kim; JongYul Kim; Min-Su Han; Hyeong Uk Mo; Jina Kim; Hyun Wook Park; Ho Jae Kwak; Jong Hyun Kim (Journal of Synchrotron Radiation)
X-ray fluorescence (XRF) is widely used to analyze elemental distributions in samples. Micro-XRF (µ-XRF), the most basic conventional XRF technique, offers good spatial resolution through precise 2D scanning with a micrometre-sized X-ray source. Recently, synchrotron based XRF analysis platforms have achieved nano-XRF with highly focused X-rays using polycapillary optics or mirrors, leveraging the excellent coherence of synchrotron radiation. However, XRF techniques are hindered by long data acquisition times (exceeding several hours) due to their point-by-point scanning approach, impeding large-area elemental mapping. Full-field XRF (FF-XRF), developed in the 2010s and based on the high brilliance of synchrotron X-rays, enables significantly shorter (less than a few minutes) data acquisition times via single-exposure imaging using a 2D X-ray detector. Nevertheless, it is constrained by relatively low spatial resolution and sensitivity. Hence, a new XRF platform is required to accommodate resolution demands to cover diverse experimental purposes. In this study, we developed a preliminary model of a novel XRF system that combines micro- and full-field XRF setups to address these limitations. This system allows easy mode switching while maintaining the region of interest of the imaging system within a single apparatus, simply by rotating the sample to face either detector depending on research purposes. We anticipate that this new XRF system will be widely utilized in various research fields as the initial XRF setup at Pohang Light Source-II.